Socio-Cultural and Educational Mission of Pedagogical Press by the Example of the Magazine „Preschool Education” - Rozgon, Viktoria (Pedagogical Discourse, 2012)
This article discusses the socio-cultural and educational value of pedagogical press, its basic functions by the example of the magazine „Preschool Education” are described.